GH replacement in patients with non-functioning pituitary adenoma (NFA) treated solely by surgery is not associated with increased risk of tumour recurrence - Arnold, J. R.; Arnold, D. F.; Marland, A.; Karavitaki, N.; Wass, J. A. H. (Clinical endocrinology (Oxford), 2009)
Summary Background  Subjects with non‐functioning pituitary adenomas (NFAs) frequently develop GH deficiency due to tumour expansion or as a consequence of tumour therapy. The safety of GH replacement (GHR) in these individuals remains unclear. Objective  To assess the effect of GHR on tumour recurrence in patients with NFAs solely treated by surgical removal. Patients and methods  The study involved all patients with NFA who presented to the Department of Endocrinology in Oxford between January 1989 and July 2005 and were treated solely by surgical removal of the tumour. Patients with follow up < 1 year were excluded. Recurrence was diagnosed on the basis of radiological appearances (detectable tumour after gross total removal or regrowth of pre‐existing residue) on regular imaging surveillance. Results  One hundred and thirty patients were included in the study, and were followed up for a mean period of 6·8 ± 4·2 years (median 5·7, range 1·2–17·6). Twenty‐three patients received GHR [16 male, 7 female, mean age at tumour diagnosis 53·7 ± 14·6 years (range 20–80)]. The mean duration of GHR was 4·6 ± 2·5 years (median 5·3, range 0·4–8·7). One hundred and seven subjects did not receive GH therapy [61 male, 46 female, mean age at tumour diagnosis 56·2 ± 14·0 years (range 20–87)]. Tumour regrowth occurred in 38 non‐GH treated subjects (36%) and 8 GHR subjects (35%). Regrowth was detected at a mean of 4·8 ± 2·8 years (range 1–11 years) in the non‐GH treated group, and at 6·5 ± 2·3 years in the GHR group. In the GHR group, recurrence occurred after a mean of 2·9 ± 2·2 years (range 0·4–5·9 years) following commencement of GH treatment. The Cox regression analysis showed that after adjusting for sex, age at tumour diagnosis, cavernous sinus invasion at diagnosis and type of tumour removal (partial or complete based on postoperative scan), GH treatment was not a significant independent predictor of recurrence (P = 0·09; hazard ratio = 0·51; 95% CI, 0·24–1·12). Conclusion   GH replacement in patients with NFA treated by surgery alone is not associated with an increased risk of tumour recurrence.